Evaluation of Renin Level and Some Hormones in Patients with Polycystic Ovarian Syndrome - Bayan Darwesh; Shereen F.Shaker; Firas Shawqi Algburi (Tikrit Journal of Pure Science)
Polycystic Ovarian Syndrome (PCOS) is one of the most frequent gynecological endocrinopathy that occurs in premenopausal females. This study aimed to investigate the relationship between PCOS and Renin Angiotensin Aldosteron system, by measuring the levels of renin, ACE, Kallikren5, FSH and LH in follicular and luteal phase, in addition to evaluating the level of kallikrein 5, which belongs to the kallikrein-kinin system associated with the renin system. The renin-angiotensin system (RAS) is well known as regulator of electrolytes and blood pressure. Renin is previously considered a major enzyme in this system. The study included 90 blood samples for married women of childbearing age between (18-45) years. These samples included 70 samples for women with polycystic ovary syndrome, which were divided into two groups (35 samples in each one), the first was withdrawn in the follicular phase, named PA, and the second in the luteal phase of the menstrual cycle named PB. As for the remaining 20 samples, they represented the control group of healthy women, which were also divided into two groups (CA and CB) as happened with the patient group. In this study, the levels of serum Renin, ACE, LH, FSH and Kallikren5 were evaluated in PCOS patients and compared with the control group in both phases. The results were analyzed by T-Test and ROC. There were no significant differences between patients and the control group in terms of ACE activity or FSH (P>0.05). The results demonstrated that LH, Renin, and Kallikren5 were higher in patient group in both phases (P<0.05). Renin Angiotensin system was affected by PCOS.